Remote working in dentistry in a time of crisis – tools and their uses. (2nd June 2020) - Parker, Kate; Chia, Matthew
Abstract : This article provides an overview of tools which enable remote working in Dentistry. It assesses the availability of tools for use in three areas of remote working in healthcare: video conference calls between professionals, apps for patients to send photographs to clinicians and platforms for telemedicine clinics and highlights the main features of common tools. CPD/Clinical Relevance: Remote working in healthcare has become increasingly popular during the COVID-19 pandemic and an understanding of how this remote working can be utilized in Dentistry, and the associated benefits, is relevant to all clinicians.